FORMATION OF CRITICAL THINKING OF FUTURE PSYCHOLOGISTS BY ANALYZING SCIENTIFIC TEXTS - Semychenko, Valentyna (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article presents the results of a theoretical analysis of the essence of the concept of "critical thinking" and an empirical study of ways of its formation in the educational process of a higher education institution. The purpose of the study was to theoretically substantiate the essence of critical thinking and, on this basis, to develop and test the methodology of forming critical thinking of future psychologist students. The research procedure was based on a system of methods: study of scientific literature, comparative generalization of leading ideas, theoretical modeling, pedagogical observation, monitoring the results of the students' activities. On the basis of the conducted bibliographic search, scientific studies on the definition of the essence of critical thinking were analyzed and summarized. its content, structure and criteria of manifestation. The relevance of creating effective techniques and methods of its formation is argued. The experience of forming critical thinking of students - future psychologists is considered. The research was conducted during 2017-2022 on the basis of the educational subject "Organization and methods of scientific research". It has been empirically confirmed that students' mastery of relevant educational material often occurs at a purely reproductive level and does not lead to the development of critical thinking. A method of involving students in the critical analysis of scientific texts has been developed and tested, which involves: critical evaluation of the works of other authors, creation and critical evaluation of one's own texts; mastering the techniques of reflective self-analysis of the products of one's own scientific activity. Examples of tasks performed by students are given. The results of the study proved that the implementation of the proposed work system is effective. The students learned the techniques of critical analysis as an organic component of the scientific process, which significantly affected the quality of their work: defining the research problem, formulating the topic, specifying the starting points of scientific research, critical analysis of theoretical approaches to the researched problem, critical attitude to the results of their work, striving for their corrections Noticeable changes occurred both at the operational level (mastering the techniques of critical analysis) and at the dispositional level (responsible attitude towards scientific activity). Based on the results of the study, conclusions were formulated about the feasibility of using the proposed method of developing students' critical thinking in the process of professional training, and prospects for the implementation of the corresponding method in other educational disciplines were outlined